GDP GROWTH, INFLATION AND UNEMPLOYMENT IN THE UZBEKISTAN ECONOMY: THEORETICAL AND EMPIRICAL ANALYSIS FOR THE PERIOD OF 2000-2024 (Prima Journal of Integrated Studies, 2026)
This research work provides an in-depth analysis of the relationship between GDP growth rates, inflation and unemployment rates based on modern macroeconomic approaches. In addition to fundamental theories such as the current transformation of the Phillips curve and the practical significance of Okun's law, the study also covers the concepts of the Keynesian multiplier and supply shocks. The uniqueness of the study is that it studies the dynamics of the Uzbek economy from 2000 to the end of 2024 in comparison with international economic trends. Therefore, the article demonstrates the impact of GDP growth on inflation based on the macroeconomic indicators forecast for 2025-2026 and the latest data from the Central Bank of the Republic of Uzbekistan and the International Monetary Fund. In particular, it is argued that economic activity exerts pressure on price growth at the initial stage, but in the long term it ensures stability due to competition and technological efficiency. An effective synthesis of classical and neoclassical views on reducing unemployment is proposed.
Keywords: GDP, inflation, unemployment, Phillips curve, Okun's law, macroeconomic stability, economy of Uzbekistan, economic analysis.